2008
DOI: 10.4314/sajas.v38i1.4106
|View full text |Cite
|
Sign up to set email alerts
|

Across flock genetic parameter estimation for yearling body weight and fleece

Abstract: Accurate genetic parameter estimates are needed upon which to perform multiple-trait across flock breed analyses. Genetic parameters for yearling body weight (BW), clean fleece weight (CFW) and mean fibre diameter (MFD) were estimated using records of 107 389 individuals (the progeny of 1 530 sires and 45 178 dams) collected between 1992 and 2004 in the South African Dohne Merino population. Fixed effects included in the model were flock-year-season-sex-management group (1 594 classes), type of birth (singles,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
2
6
0
Order By: Relevance
“…The lack of differences in fleece weight between the Dohne Merino and SAMM breeds may result because of compensatory differences in bodyweight. This hypothesis is supported by the observation of a positive correlation (r = 0.32) between yearling weight and clean fleece weight in Dohne Merinos (Van Wyk et al, 2008). As yearlings, ram lambs presented greater wool growth than ewe lambs.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The lack of differences in fleece weight between the Dohne Merino and SAMM breeds may result because of compensatory differences in bodyweight. This hypothesis is supported by the observation of a positive correlation (r = 0.32) between yearling weight and clean fleece weight in Dohne Merinos (Van Wyk et al, 2008). As yearlings, ram lambs presented greater wool growth than ewe lambs.…”
Section: Resultsmentioning
confidence: 70%
“…Such coarse wools with low comfort factors are not suitable for fabrics that have direct contact with the skin, and are more suited to the manufacturing of carpets and blankets. The national average fibre diameter for Dohne Merino stud ewes was reported to be 19.4 µm (Van Wyk et al, 2008). Snyman et al (1998) reported that fibre diameter of Merino ewes varied (19.8 -23.0 µm) among South African research flocks.…”
Section: Resultsmentioning
confidence: 99%
“…In the Dohne Merino, weaning weights were commonly recorded and used for preliminary index selection, but seldom submitted to the registration authority. Performance recording in this breed concentrated on yearling liveweight and fibre traits, as is evident from publications by Swanepoel (2006) and Van Wyk et al (2008). However, birth registrations and weaning weights are used to generate reproduction records in the NSSIS.…”
Section: Breeding Sheep In South Africamentioning
confidence: 99%
“…The integration of data in the 1990s from various breeders in a common database for the important breeds resulted in the first across-flock genetic analysis for South African Merinos in 1998 . Data from the scheme have since been used in across-flock analyses of several breeds, namely Dohne Merino (Van Wyk et al, 2008;Olivier & Cloete, 2011), Merino , Dormer, Ile de France and Merino Landsheep (Zishiri et al, 2014) and the Dorper (Olivier & Cloete, 2006;Zishiri et al, 2013a). Research continues on these breeds, and the national analyses are improved as superior techniques and methods become available.…”
Section: Breeding Sheep In South Africamentioning
confidence: 99%
See 1 more Smart Citation